The Internalisation of Hisbah Principles in OJK Regulations on Islamic Banking Compliance Supervision - Neneng Nurhasanah (al-Uqud : Journal of Islamic Economics, 2021)
One of OJK duties and authorities is to supervise sharia compliance of Islamic banking operations in Indonesia. However, this role is still not optimal to conduct because the existence of DPS is considered sufficient to perform it. This study aimed to examine OJK arrangement on Islamic banking compliance supervision, adjustment on Islamic compliance supervision after switching from BI to OJK, and internalisation of hisbah principles in these regulations. This research used the normative juridical method, compiled positive law related to Islamic Banking supervision and compared it with hisbah principles implemented in the Islamic governance history as a basis for supervision internalised in OJK regulations and legislation. The result showed that (1) OJK regulates Islamic Banking compliance supervision through the rules of DPS establishment in Islamic Banking as the responsible party, received the DPS and SKAI reports periodically, and conducted audits by sampling on the application of sharia aspects; (2) several Islamic Banking supervision regulations still require harmonisation, especially those issued by BI; (3) five hisbah principles exist in the OJK regulations: transparency, accountability, responsibility, professionalism, and fairness.